2013
DOI: 10.3109/02699052.2013.794960
|View full text |Cite
|
Sign up to set email alerts
|

Post-acute assessment programme for patients with traumatic brain injury: Measuring the gap between patients’ expectations on entering and end of programme recommendations

Abstract: The discrepancy between patients' expectations and recommendations is in part due to the cognitive disorders; long-term rehabilitation programmes should focus on this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Most immediate objectives of new research may be to confirm these results and improve the technology packages, as suggested above (Kennedy, 2005 ; Barlow et al, 2009 ; Goodwin, 2010 ). Other important goals may be to investigate (a) participants’ satisfaction with the programs (i.e., by including participants and programs like those of Studies II and III); and (b) families and staff’s opinions about the programs and suggestions for improving them (Lancioni et al, 2006 ; Callahan et al, 2008 ; Ripat and Woodgate, 2011 ; Lamontagne et al, 2013 ; Lenker et al, 2013 ; Lindstedt and Umb-Carlsson, 2013 ; Pouliquen et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most immediate objectives of new research may be to confirm these results and improve the technology packages, as suggested above (Kennedy, 2005 ; Barlow et al, 2009 ; Goodwin, 2010 ). Other important goals may be to investigate (a) participants’ satisfaction with the programs (i.e., by including participants and programs like those of Studies II and III); and (b) families and staff’s opinions about the programs and suggestions for improving them (Lancioni et al, 2006 ; Callahan et al, 2008 ; Ripat and Woodgate, 2011 ; Lamontagne et al, 2013 ; Lenker et al, 2013 ; Lindstedt and Umb-Carlsson, 2013 ; Pouliquen et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%